Assessing the renal response in patients with potassium disorders: a shift in emphasis from the TTKG to the urine K+/creatinine ratio - Halperin, Mitchell L (African Journal of Nephrology, 2017)
This article briefly reviews the reasons for replacing the transtubular K+ gradient (TTKG) with the urine K+/creatinine ratio, as a tool for evaluating the response of the kidney in patients with potassium disorders. An appreciation of the magnitude and importance of the intrarenal recycling of urea led to the realization that a large amount of urea is reabsorbed daily in the terminal collecting duct and that this renders invalid the assumption, used by the TTKG, that there is minimal solute reabsorption downstream of the cortical collecting duct (CCD). The urine-to-plasma osmolality ratio can therefore not be used to calculate the volume of fluid exiting the CCD nor the concentration of K+ in the luminal fluid in this nephron segment. We now recommend the use of the K+/creatinine ratio in random urine samples to estimate the rate of K+ excretion. A ratio of less than 1.5 mmol K+/mmol creatinine would be expected if the kidney is responding appropriately to hypokalaemia from a non-renal cause, and a ratio greater than 20 mmol K+/mmol creatinine would be appropriate as the renal response to hyperkalaemia.